2016
DOI: 10.1021/acsmedchemlett.6b00137
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Steroidal Androgen Receptor Degrading Agents Inspired by Galeterone 3β-Imidazole Carbamate

Abstract: Degradation of all forms of androgen receptors (ARs) is emerging as an advantageous therapeutic paradigm for the effective treatment of prostate cancer. In continuation of our program to identify and develop improved efficacious novel small-molecule agents designed to disrupt AR signaling through enhanced AR degradation, we have designed, synthesized, and evaluated novel C-3 modified analogues of our phase 3 clinical agent, galeterone (5). Concerns of potential in vivo stability of our recently discovered more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The new NGGAs (VNPP414 and VNPP433-3β) were identified from in vitro anti-proliferative activities of our in-house compounds assessed in several PC cell lines, including LNCaP, C4-2B, and CWR22Rv1 (22Rv1) [8]. Because drug resistance remains a major clinical challenge in PC therapy [32,33,34,35,36,37], we compared the efficacies of Gal, VNPP414, and VNPP433-3β against several PC drugs-resistant cell lines, including enzalutamide (MDV-3100)-resistant (MR49F), mitoxantrone-resistant (CWR-R1(MTX), and docetaxel-resistant CWR-R1 (10E) PC cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The new NGGAs (VNPP414 and VNPP433-3β) were identified from in vitro anti-proliferative activities of our in-house compounds assessed in several PC cell lines, including LNCaP, C4-2B, and CWR22Rv1 (22Rv1) [8]. Because drug resistance remains a major clinical challenge in PC therapy [32,33,34,35,36,37], we compared the efficacies of Gal, VNPP414, and VNPP433-3β against several PC drugs-resistant cell lines, including enzalutamide (MDV-3100)-resistant (MR49F), mitoxantrone-resistant (CWR-R1(MTX), and docetaxel-resistant CWR-R1 (10E) PC cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have demonstrated that Gal and the NGGAs target the androgen receptor (including its splice variant AR-V7) and Mnk1/2-eIF4E (eIF4E phosphorylation at serine209) signaling pathways (dual AR/Mnk1/2 inhibitors) and that the NGGAs are more effective than Gal [8,9,11]. Because the androgen receptor is a negative regulator of eIF4E phosphorylation at serine 209 [19,20], our new class of compounds can effectively inhibit Mnk/eIF4E in addition to AR transcriptional activity with the potential to negate negative feedback to prevent PC progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galeterone and analogs (VNPT55, VNPP414 and VNPP433-3β) were designed and synthesized in our laboratory [ 26 , 68 , 69 ] and dissolved in DMSO. Gemcitabine was purchased from Sigma Aldrich.…”
Section: Methodsmentioning
confidence: 99%
“…Also galaterone (3, Figure 4), a known CYP17 inhibitor and AR antagonist, promotes the proteasomal degradation of both AR and its ligand-independent variants AR-V7 and Arv567es [152,153] .…”
Section: Seviteronel (5mentioning
confidence: 99%